A Systems Approach to Monitoring Antimicrobial Consumption and Use in Uganda - Miss Vivian Twemanye; Ms Harriet Akello; Mr Moses Mukiibi; Mr Richard Walwema; Dr Jonathan Mayito; Dr Morries Seru (International Journal of Infectious Diseases)
Introduction: The Antimicrobial resistance (AMR) threat necessitates coordinated and complementary systems to effectively monitor antimicrobial consumption and use (AMUC). The current approaches to standardize data collection don't capture the complexities of AMUC patterns and the diverse influencing factors. We present Uganda's experience in the adoption of the six building blocks of the WHO Health System Framework in monitoring AMUC. Methods: Uganda's approach recognizes that AMUC is influenced by healthcare delivery, governance structures, financing mechanisms, workforce capacity, and information systems. Furthermore, it acknowledges the critical role of supply chain for essential medicines in shaping AMUC patterns. Uganda, therefore, instituted an approach that integrates data from multiple sources, such as imports, distribution and individual patient use for a comprehensive understanding of AMUC dynamics. The leadership, governance structures and coordination mechanisms were defined; and their roles and responsibilities anchored in policies to improve appropriate AMUC. Continuous quality improvement (CQI) policies ensure use of the data for effective use of resources in averting consequences of AMR. Results: Ministry of Health (MoH) established an advisory group on appropriate medicine use that works collaboratively with other national structures to guide on the availability and appropriate use of antimicrobials. A national policy to ensure the implementation of antimicrobial stewardship at facilities has fostered the appointment and functionalizing of multidisciplinary medicines and therapeutic committees in health facilities. These policy frameworks have created budget lines and opportunities to prioritize the interventions that improve antibiotic use. This policy and the national guidelines for monitoring AMUC have enabled health facilities to conduct regular antimicrobial use surveys. Through continuous training and support supervision, MoH has also built capacity for data storage, analysis and use for CQI. MoH has been able to generate consumption data contributing to global databases such as WHO GLASS as well as contextualize the extent of the burden of irrational use of antibiotics. Finally, interdisciplinary collaboration has ensured involvement of stakeholders at national, facility and community levels. Discussion: By adopting a systems approach, Uganda has enhanced the accuracy, relevance, and sustainability of surveillance and optimal use of antimicrobials. Understanding the complex interactions between various stakeholders, policies, and practices has informed evidence-based interventions to mitigate AMR. Conclusion: A systems approach fosters a holistic understanding of the dynamics of AMUC, which contributes to building resilient health systems capable of effectively addressing emerging health threats.